The Influence Of Person-Job Fit, Person-Organization Fit And Organizational Support On Organizational Commitment In Educators And Educational Personnel Boyolali University - Alean Kistiani Hegy Suryana; Aham Ginanjar Rahayu; Unna Ria Safitri; Nur Asih Triatmaja; Yunita Niqrisah Dwi Pratiwi (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
The purpose of this study is to investigate the impacts of organizational support, person-job fit, and person-organization fit, both separately and in combination, on organizational commitment at Boyolali University's academic and administrative personnel. Saturated sampling was used to get the data from a questionnaire, with 58 individuals in the overall sample size. This study used a case study technique in conjunction with quantitative research methodology. Using SPSS 25, the instrument data and hypothesis testing were carried out. The findings showed that, with a sig. value of 0.116>0.05 and a t-value of 1.599<t-table of 1.672, the variable (X1) Person-Job Fit had no significant impact on the variable (Y) Organizational Commitment. However, with a sig. value of 0.001<0.05 and a t-value of 3.409>t-table of 1.672, the variable (X2) Person-Organization Fit had a positive and significant effect on the variable (Y) Organizational Commitment. Additionally, with a sig. value of 0.127 > 0.05 and a t-value of 1.549 < t-table of 1.672, the variable (X3) Organizational Support had no discernible impact on the variable (Y) Organizational Commitment. With a sig. value of 0.000<0.05, the F-test showed that Organizational Support, Person-Job Fit, and Person-Organization Fit all together had a significant influence on Organizational Commitment. An adjusted R2 value of 0.750 was found in the determination test, indicating that 75% of the variance in the dependent variable can be explained by the independent factors, with the remaining 25% being impacted by other independent variables.